Rin-in comb wheels of the wheel pair of the car when moving on a curve section of the path - Djabbarov Shukhrat; Abdirakhmanov Jamshid; Abdullaev Bakhrom; Namozov Sokhib; Yuldoshov Rustam; Ergasheva Vasila (E3S Web of Conferences, 2023)
In the article, using the classical provisions of theoretical mechanics, various methods of constructing a computational model of rolling in the wheel crest of a wheelset of a wagon from when moving rolling stock along a curved section of track are presented.